Comparative study on heat transfer performance of γAl2O3−C2H6O2 and γAl2O3−H2O nanofluids via Prabhakar fractional derivative model for MHD channel flows. (October 2022) - Asifa,; Anwar, Talha; Kumam, Poom; Muhammad, Shah
Abstract: The prime focus of this work is to investigate the thermal behavior of ethylene glycol and water based γ Al 2 O 3 nanofluids for free convective flow through a stationary channel. The imposition of uniform magnetic effects is assumed in the normal direction of the vertical channel, which is nested in a porous material. The Fourier law for estimation of the thermal flux is generalized by dint of the Prabhakar fractional derivative. The viscosity and thermal conductivity of considered nanofluids are measured by employing experimentally evaluated relations of these quantities. Some dimension-free quantities are introduced and the resulting generalized unit-less fractional governing equations are solved analytically with the assistance of the Laplace transformation. Several tables and graphical illustrations are provided to anticipate the influence of various factors on flow distribution and temperature profile. A comprehensive study comprised of multiple parts such as anticipation of the thermal performance, variation in skin friction coefficient, and parametric impacts on thermal and velocity profiles is conducted to deeply analyze and compare the behavior of γ Al 2 O 3 − C 2 H 6 O 2 and γ Al 2 O 3 − H 2 O nanofluids. The outcomes suggest that there is a noteworthy enhancement in heat transfer rate due to an increase in fractional parameters. The enhancement in volume proportion of nanoparticles reduces the velocity of nanofluid. Moreover, the improvement in heat transfer rate of ethylene glycol and water due to the dispersion of γ Al 2 O 3 nanoparticles is 7.98% and 10.68% respectively.